Prognostic factors in elderly patients with acute myeloid leukemia - Postic, Anka; Virijevic, Marijana (Srpski medicinski časopis Lekarske komore, 2021)
Background: Acute myeloid leukemia (AML) is characterized by pathological proliferation of myeloid lineages. It predominantly occurs in patients over 60 years of age, whose outcome is considerably worse comparing to younger patients.Aim: Analysis of clinical characteristics of older patients with AML and their impact on achieving complete remission (CR), overall survival (OS), early mortality (EM) and relapse.Materials and methods: The study included 94 patients with AML, treated with chemotherapy and palliative therapy, whose informations were taken from their medical history. The following clinical features were studied as risk factors for OS, KR, relapse and EM: leukocytes, serum lactate dehydrogenase (LDH), ECOG (Eastern Cooperative Oncology Group), European LeukemiaNet cytoplasmic risk group, HCT-CI (hematopoetic cell transplantation- comorbidity index) and NPM1/FLT3-ITD (Nukleofosmin/FLT3-internal tandem mutation) molecular status. For the identification of prognostic factors, a Cox regression analysis was used.Results: The average age of patients was 69 years (range: 65-87). CR was achieved in 23 (24.5%) patients of 50 (53.2%) who received intensive chemotherapy, with relapse occurring in 17 (70.8%). EM was reported in 17 (18.1%) patients. Patients with ECOG PS > 2 had statistically significant lower OS than patients with ECOG PS < 2 (p = 0.030). Patients with HCT-CI > 3 had a poorer OS than patients with HCT-CI < 3 (p = 0.040). Serum LDH > 450 U/I was found to be a poor prognostic factor for the OS compared to LDH < 450U/I (p = 0.044).Conclusion: Older AML patients with poorer ECOG PS, high HCT-CI, increased LDH levels have a poorer OS.
Keywords: acute myeloid leukemia; elderly patients; overall survival; prognostic factors